Experimental and theoretical investigations of visible spectra of W12+. (March 2022) - Lu, Q.; Fu, N.; Yan, C.L.; Qu, F.H.; Yang, Y.; Wang, K.; Chen, C.Y.; Zou, Y.; Xiao, J.
Highlights: To provide atomic data for low charged tungsten ions relevant to fusion research, by the collisional-radiative modeling (CRM) capabilities of the Flexible Atomic Code (FAC), 10 visible lines from W 12+ that were previously reported with a compact electron-beam ion trap [Kobayashi et al., Phys Rev A 2015;92:022, 510] are identified. Supplementary experiments are conducted using the Shanghai high-temperature superconducting electron-beam ion trap to search for one strong missing line (predicted by the CRM calculation) that was not observed in the previous studies. The previous observations are confirmed and one line at 660.3 nm is newly reported. Large-scale calculations for the excitation energies of the 50 lowest levels arising from 4 f 14 5 s 2, 4 f 13 5 s 2 5 p and 4 f 12 5 s 2 5 p 2 of W 12+ are performed using the FAC and GRASP codes. The data from the two independent calculations agree well with each other, with an average deviation of ∼800 cm −1 . The results are compared with the experimental values to verify our line identifications. Except for one line at ∼540.5 nm, the wavelength differences between our experimental and theoretical values are ∼1.5% on average. Abstract: To provide relevant atomic data for fusion research, a collisional-radiative model (CRM) simulation is conducted using the Flexible Atomic Code (FAC) to identify the 10 visible lines for W 12+ measured with a compact electron-beam ion trap (EBIT) [Kobayashi et al., Phys Rev A 2015;92:022510]. To search for one missing strong visible line predicted from the CRM results, additional experiments are performed using EBIT devices at the Shanghai EBIT Laboratory. Also, large-scale calculations are performed using the FAC and GRASP codes to check the line identifications and investigate electron-correlation effects for W 12+ . The excitation energies for the 50 lowest levels arising from 4 f 14 5 s 2, 4 f 13 5 s 2 5 p and 4 f 12 5 s 2 5 p 2 of W 12+ are presented for the first time, with an average deviation of ∼800 cm −1 . The resulting theoretical wavelengths agree well with the experimental values (with an average deviation of ∼1.5%) except for one 540.5 nm line, which calls for further theoretical studies.